تأثير برنامج تدريبي لتحسين القدرة العضلية لناشئي كرة السرعة - أبو المعاطي، هبة روحي عبده; عزت، أحمد حسن حسين; أبو الدهب، الشيماء علي; سليمان، منار خلف (جامعة طنطا - كلية التربية الرياضية, 2022)
يهدف البحث إلى تطوير القدرة العضلية بالحد من العجز الثنائي لليد الغير ضاربة لناشئي كرة السرعة، واستخدم الباحثون المنهج التجريبي باستخدام التصميم التجريبي لمجموعة واحدة باستخدام القياس القبلي والبعدي، وتم اختيار عينة البحث الأساسية بالطريقة العمدية من ناشئي كرة السرعة بنادي زفتي الرياضي ويبلغ قوامها (16) ناشئ كرة السرعة، وكان من أهم النتائج أن البرنامج التدريبي المقترح أظهر تأثيراً إيجابيا في تطوير القدرة العضلية بالحد من العجز الثنائي لليد الغير ضاربة وتحسين مستوى الأداء المهارى لناشئي كرة السرعة. The research aims to develop the muscular ability by reducing the bilateral deficit of the non-hitting hand of the speedball juniors, and the researcher used the experimental method using the experimental design for one group using the tribal and remote measurements, and the basic research sample was chosen in a deliberate way from the speedball juniors at Zefta Sports Club, and its strength is (16) speedball junior, and the most important results were: the proposed training program showed a positive effect in developing the muscular ability by reducing the bilateral deficit of the non-hitting hand and positive effect in improving the skill level of speedball juniors.
Keywords: البرامج التدريبية -- الأداء المهاري -- اللياقة البدنية -- ناشئو كرة السرعة